Transcriptional repression of specific host genes by the mycovirus Cryphonectria hypovirus 1. - Kazmierczak, P (1996)
The hypovirus CHV1, which infects the plant-pathogenic fungus Cryphonectria parasitica, causes a distinct range of symptoms in its host that include reduced virulence expression, reduced sporulation, and reduced pigmentation. The virus, however, has little or no effect on fungal growth in culture. The visual symptoms are associated with reduced accumulation of a small number of host mRNAs and proteins. Four of the host genes encoding these down-regulated mRNAs have been characterized; they include two genes encoding a fungal sex pheromone (Vir1 and Vir2), a gene encoding an extracellular laccase (Lac1), and a gene encoding a cell wall hydrophobin (Crp). Expression of most other host proteins appears to be unaffected by the virus. These four genes can serve as reporter genes in studies of the effect of the virus on host gene expression. It is hypothesized that the four genes are coordinately down-regulated by the virus and probably are associated in a regulatory cascade. This hypothesis was tested by measuring the relative transcription rate of each gene in virus-infected and uninfected isogenic strains of the fungus by using nuclear run-on assays. The effects of the virus on transcription of these genes generally mirrored the observed effects of the virus on relative accumulation of the mRNAs of each gene. Although repressed transcription cannot account for all of the effects of the virus on mRNA accumulation of these four reporter genes, it is the predominant effect.